(3Md eSCdI GdCbHGd hGdEOHGQs - (3SfN RGOg chfHGfj, CHh ESMGbs
(3ChdgG (B:s
(3ddg Gdefg Ydi eG jJjM ef eaGJjM QMeJg dYHGOg hHYO adbO QCjJ ef CYXe GdQHGf hCaGUd GdCYjGf jJSCdhf Yf eGdI GdEbHGd GdEOHGQ s
(3BNQgG (B:s
(3aQSe TcdGf Whd CMOgeG Ci bWQg GdChd bhS ef fUa GdfgGQ MGeO Hf ddg Ydi fhGdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(1 / 2417) s
Keywords: (3Gdadcs